Applying Laffer Curve on Profit Tax Collected from Jordanian Islamic and Traditional Banks - BaniEssa, Mohammad; Al Badarin, Abdalla (Jordan Journal of Economic Sciences, 2020)
The study aims at estimating the Laffer curve for the tax profits of Islamic and traditional banks in Jordan, by building a logarithmic model, and using the OLS method to estimate the Laffer curve, and determine the optimal rate of banks profit tax. The study found that rates of profit tax on Jordanian banks in general and Jordanian Islamic banks in particular are high. The study showed that the actual tax rate on the profits of all Jordanian banks was (28.4%), while the optimum rate was (23.5%). It also found that the actual rate of tax on profits of Islamic banks was (31.6%), while the optimum rate was (19.8%).The study showed that the actual rate of traditional banks was (27.8%), while the optimum rate was (26.1%).